Intensity of hypertensive exposure in young adulthood and subclinical atherosclerosis in middle age: Evidence from the CARDIA study - Xiong, Zhenyu; Li, Jiaying; Lin, Yifen; Ye, Xiaomin; Xie, Peihan; Zhang, Shaozhao; Liu, Menghui; Huang, Yiquan; Liao, Xinxue; Zhuang, Xiaodong (Frontiers in Cardiovascular Medicine, 2022)
Background Chronically high blood pressure (HBP) is a known risk factor for cardiovascular diseases. We measured the intensity of hypertensive exposure in young adults and calculated its prognostic significance for subclinical atherosclerosis in middle age. Methods The Coronary Artery Risk Development in Young Adults (CARDIA) study enrolled 5,115 healthy black and white Americans who were 18–30 years old at baseline (1985–1986). The intensity of hypertensive exposure was calculated as the area under the curve (mm Hg × years) from baseline to year 15. Coronary artery calcium (CAC) was identified at years 15, 20, and 25, and intima-media thickness (IMT) was identified at year 20. Results At baseline, the mean age was 40.1 years; 55.1% of participants were women, and 46.5% were black. After adjustment, cumulative systolic BP (SBP) was positively associated with CAC [hazard ratio (HR) = 1.23 (1.14, 1.32)] and IMT [β = 0.022 (0.017, 0.028)]. For CAC, the C-statistic for cumulative SBP was 0.643 (0.619, 0.667); compared to baseline SBP, the net reclassification index (NRI) of cumulative SBP was 0.180 (0.115, 0.256) and the integrated discrimination improvement (IDI) was 0.023 (0.012, 0.036). For IMT, the C-statistic for cumulative SBP was 0.674 (0.643, 0.705), the NRI was 0.220 (0.138, 0.305), and the IDI was 0.008 (0.004, 0.0012). Conclusion Greater intensity of hypertensive exposure in early adulthood is associated with subclinical atherosclerosis in middle age and provides better prognostic value than baseline BP for early cardiovascular risk.